The validity of the Computer Face Scale for measuring pediatric pain and mood. Issue 2 (13th October 2012) - Cravero, Joseph P.; Fanciullo, Gilbert J.; McHugo, Gregory J.; Baird, John C.; Lonnqvist, Per‐Arne
Summary Objective The aim was to assess the validity of the Computer Face Scale. Methods Forty children (5–13 years old) rated pain and mood prior to and twice following tonsillectomy. The children used the Computer Face Scale to adjust a cartoon face to rate pain and mood. During sessions one and two, the children also chose an expression on the Wong‐Baker Faces Scale to rate their pain, and they reported their mood verbally on a seven‐point scale. Results On average, the children reported no pain and a positive mood prior to surgery. Soon after surgery, they reported mild pain and a slightly negative mood. An hour later, they reported decreases in pain and return to a positive mood. The differences between presurgery and postsurgery ratings were statistically significant (P ≤ 0.001) for all measures. The correlation between the two mood measures was 0.88 before surgery and 0.78 afterward. The correlation between the two measures of pain was 0.83 after surgery (P's < 0.001). Conclusions The results support the validity of the Computer Face Scale. The mean ratings of pain and mood followed the expected pattern from pre‐ to postsurgery, and there was a significant association between ratings obtained by different methods. The Computer Face Scale provides a simple‐to‐use scale with more resolution and electronic capture, which may provide advantages in numerous clinical and research applications.